Racial disparities in hypertension subtype prevalence over the lifecourse: evidence of accelerated arterial ageing in a population representative cross-sectional study - Michelle C Odden; Alexis N. Reeves (BMJ Public Health, 2025)
Introduction Racially minoritised populations, particularly Black individuals, have been shown to have an earlier average age of onset of hypertension (elevated systolic and/or diastolic blood pressure) compared with White individuals potentially due to ‘weathering’ or accelerated health declines due to the cumulative impact of marginalisation over the lifecourse. Systolic blood pressure is more reactive to stress, increases linearly with age indicative of arterial ageing and is more highly associated with cardiovascular morbidity and mortality versus diastolic blood pressure. However, little research has examined racial differences in isolated systolic hypertension. This study examines the race/gender differences in the prevalence of two mutually exclusive manifestations of hypertension: diastolic hypertension (ie, elevated diastolic with or without elevated systolic blood pressure) and isolated systolic hypertension (increased systolic only) over the lifecourse.Methods The National Health and Nutrition Examination Survey from 2016 to 2020, a US-based population representative cross-sectional study, was used in weighted multinomial logistic regression models to estimate age-specific prevalence of hypertension subtypes by race/gender subgroups controlling for socioeconomic status and anti-hypertensive use. Outcomes were diastolic (diastolic ≥90 mm Hg with/without systolic ≥140 mm Hg) and isolated systolic (systolic ≥140 mm Hg and diastolic <90 mm Hg) hypertension.Results The prevalence of diastolic hypertension increased until midlife and then decreased with increasing age, while the prevalence of isolated systolic hypertension increased throughout the lifecourse. Black women had nearly triple the prevalence of diastolic hypertension from 20 to 45 years where the disparity lessens to double the prevalence and continues to lessen with increasing age and 2–3 times the prevalence of isolated systolic hypertension as early as 35 years with continued disparity at older ages. Black men had nearly double the prevalence of diastolic hypertension from 35 to 65 years and at least double the prevalence of isolated systolic hypertension throughout the lifecourse with the widest disparities at 40 years. Disparities attenuated but remained statistically significant with adjustment for socioeconomic status.Conclusions Results suggest that isolated systolic hypertension is a dominant and important form of hypertension starting in midlife (~50–60 years); however, indicative of potential earlier arterial ageing, Black men and women’s increased prevalence may start as early as 35 and 45 years, respectively.